STRATEGI KOMUNIKASI UNTUK PENGEMBANGAN POTENSI WANITA MELALUI KOMUNITAS VIRTUAL (Studi Kasus Sharing Session Tema Wanita melalui Whatsapp Group Ciledug Female Community ) - Permata, Sandy (Jurnal Visi Komunikasi, 2023)
Nowadays, with the development of information and communication technology, all sectors of life are facilitated by the presence of the internet. . The use of social media as a new media that currently intersects with life and everyday life in all aspects of people's life also certainly has a very high impact on the emergence of new knowledge, both positive in nature or can also provide new experiences that have never been encountered in the real world and Various kinds of virtual communities emerge with various social goals in the group. The urgency of this research is to see the creation of a communication strategy for a virtual group of women through the WhatsApp application with the aim of providing maximum information and education to women, especially those who join the Ciledug Female Community.This research was conducted using a qualitative case study method with in-depth interview data collection techniques and non-participant observation. From the results of the analysis carried out, the Ciledug Female Community has carried out Sharing Session activities in the form of a good and planned communication strategy in accordance with the objectives that the community wants to produce, namely increasing knowledge and understanding of community members in various things that have never been obtained in space other virtual community spheres. The form of communication carried out in the Virtual Ciledug Female Community, especially at the Sharing Session, is sharing on social media, optimizing messages, managing conversations between resource persons and members and creating engagement between sources, committees and CFC members.Keywords: Communication Strategy, New Media, Virtual Community